White matter microstructure relates to motor outcomes in myotonic dystrophy type 1 independently of disease duration and genetic burden - Koscik, Timothy R. (Sci Rep, 2021)
Deficits in white matter (WM) integrity and motor symptoms are among the most robust and reproducible features of myotonic dystrophy type 1 (DM1). In the present study, we investigate whether WM integrity, obtained from diffusion-weighted MRI, corresponds to quantifiable motor outcomes (e.g., fine motor skills and grip strength) and patient-reported, subjective motor deficits. Critically, we explore these relationships in the context of other potentially causative variables, including: disease duration, elapsed time since motor symptom onset; and genetic burden, the number of excessive CTG repeats causing DM1. We found that fractional anisotropy (a measure of WM integrity) throughout the cerebrum was the strongest predictor of grip strength independently of disease duration and genetic burden, while radial diffusivity predicted fine motor skill (peg board performance). Axial diffusivity did not predict motor outcomes. Our results are consistent with the notion that systemic degradation of WM in DM1 mediates the relationship between DM1 progression and genetic burden with motor outcomes of the disease. Our results suggest that tracking changes in WM integrity over time may be a valuable biomarker for tracking therapeutic interventions, such as future gene therapies, for DM1.